2017
DOI: 10.1155/2017/1478625
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene Inhibits Propagation of Chlamydia Infection

Abstract: Chlamydiaceae is a family of obligate intracellular pathogenic bacteria with similar developmental cycles and cell biology responsible for a wide range of diseases in different hosts including genital and eye inflammatory diseases, arthritis, and inflammatory diseases of the respiratory and cardiovascular systems. In the present paper, we report that lycopene, one of the main dietary carotenoids, which is present in tomato and some other fruits, has a strong inhibitory effect on C. trachomatis and C. pneumonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
(26 reference statements)
1
3
0
1
Order By: Relevance
“…Moreover, decline in oxidized LDL and IOD values caused by GA lycopene supplementation was accompanied by a threefold reduction in Chlamydia pneumoniae IgG which is known to be an important marker of oxidative stress and inflammation in cardiovascular patients (Di Pietro, Filardo, Falasca, Turriziani, & Sessa, ). This observation is in a good agreement with our recently published results (Zigangirova et al., ) revealing a strong inhibitory effect of lycopene on C. trachomatis and C. pneumoniae infections in cultured cells. However, under the conditions used in our study, we did not observe any significant changes in the markers of oxidation and inflammation or in cardiovascular parameters for patients supplemented with lactolycopene, although there was a half‐fold increase in serum lycopene level in patients with cardiovascular disease after 1 month of supplementation.…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, decline in oxidized LDL and IOD values caused by GA lycopene supplementation was accompanied by a threefold reduction in Chlamydia pneumoniae IgG which is known to be an important marker of oxidative stress and inflammation in cardiovascular patients (Di Pietro, Filardo, Falasca, Turriziani, & Sessa, ). This observation is in a good agreement with our recently published results (Zigangirova et al., ) revealing a strong inhibitory effect of lycopene on C. trachomatis and C. pneumoniae infections in cultured cells. However, under the conditions used in our study, we did not observe any significant changes in the markers of oxidation and inflammation or in cardiovascular parameters for patients supplemented with lactolycopene, although there was a half‐fold increase in serum lycopene level in patients with cardiovascular disease after 1 month of supplementation.…”
Section: Discussionsupporting
confidence: 94%
“…Intake of lycopene rich food has been linked to lower prevalence of cardiovascular disease, stroke [1] and some forms of cancer [2, 3]. Limited interventional clinical studies have indicated its therapeutic ability to slow down development of carotid atherosclerosis [4], anti-infective and anti-inflammatory properties [5], improvement of parameters associated with prostate hyperplasia [6], benefit in management of prostate cancer [7] and help to protect skin from UV damage [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Petyaev (2016) and Chen et al (2015), respectively, reported lycopene deficiency in ageing and prostate cancer in human. Zigangirova et al (2017) reported that lycopene inhibits propagation of Chlamydia red blood cells (RBC) osmotic fragility and lipid peroxidation in animals by lycopene. Moreover, Pandir et al (2016) reported the effect of lycopene at 4 and 40 mg/kg body weight against oxidative damage induced by furan.…”
Section: Introductionmentioning
confidence: 99%